Copper removal by cellulose xanthogenate derived from Imperata cylindrica L. leaf powder / Zubir bin Othman - Othman, Zubir (2013)
The efficiency of cellulose xanthogenate derived from Imperata cylindrica L. leaf powder (CXIC) for removing Cu(II) from aqueous solutions has been investigated. The effects of physicochemical parameters on biosorption capacities such as biosorbent dosage, pH, initial concentration of Cu(II) and contact time were studied. The biosorption capacities of CXIC increased with the rise in pH and Cu(II) concentration but decreased with the increase in biosorbent dose. Biosorption of Cu(II) was considered fast as the time to reach equilibrium was 60 min. Two kinetic models; pseudo-first order and pseudo-second order were applied to analyse the Cu(II) biosorption process, and it was found that the pseudo-second order fitted well with the biosorption data with correlation coefficients (R2) greater than 0.99. In order to understand the mechanism of biosorption, spectroscopic analyses involving Fourier Transform Infrared (FTIR) and Scanning Electron Microscope (SEM) coupled with Energy Dispersive Spectroscopy (EDS) were carried out on the CXIC. FTIR analyses revealed that -OH, -NH, C=C, COO-, -CS2 and C-O-C as the major functional groups involved in the binding of Cu(II) and complexation was one of the main mechanisms for the removal of Cu(II) as indicated by FTIR spectra. Ion exchange was another possible mechanism involved as indicated by EDS spectra since there was a release of light metal ions during the biosorption of Cu(II). The isotherm study indicated that the CXIC fitted well with the Langmuir model compared to the Freundlich model. Based on the Langmuir model, the maximum biosorption capacity was 18.59 mg.g-1 .